Az alapfokú zeneoktatás jellemzői virtuális térben a Covid-19 ideje alatt: A kutatás bemutatása (Training and Practice : Journal of Educational Sciences, 2024)
The Doctoral Program on Educational Sciences of the University of Debrecen, the Faculty of Music and the Art Pedagogy Research Group of the Foundation for the Art of Future launched research in the fall of 2021, investigating the role of parents in children's musical education in both real and virtual space. The data collection took place in the spring of 2022 with the support of the Research Institute of Art Theory and Methodology of Hungarian Academy of Arts. The self-made measuring instrument, containing closed and open questions, focused on the opinions of parents whose children play an instrument in elementary art school or attend private singing lessons. The opinion of the respondents (N=458) can be interesting, as during this period they could see a little more into the teaching of music and see things from a different perspective. The survey also looked at parents' music listening habits and the factors that influence them. The results showed that those who had been involved in music more often attended concerts of light and classical music and listened to music not only in a contextual way but also for its own sake, while those who had never received music education tended to listen to music only as a back-up during other activities.
Keywords: instrumental education; online education; music education